Principle and performance of orbital angular momentum communication of acoustic vortex beams based on single-ring transceiver arrays - Li, Xinjia; Li, Yuzhi; Ma, Qingyu; Guo, Gepu; Tu, Juan; Zhang, Dong (Journal of applied physics, 2020)
As the main way of underwater data transmission, acoustic communication is still limited by the low-level signal-to-noise ratio and channel capacity. The orbital angular momentum (OAM) based acoustic communication of acoustic vortex (AV) provides a new dimension to data transmission with an expanded channel capacity. Theoretical analyses and experimental measurements for the OAM communication of AV beams based on single-ring transceiver arrays are studied in air. Coaxial multi-OAM AV beams are generated with multiple topological charges encoded by the binary ASCII codes of various letters. The OAM modes of the AV beams are decoded with limited acoustic pressures detected by the single-ring receiver array around the vortex center based on the orthogonal property. It is proven that the channel capacity of the communication system can be increased effectively by the OAM modes of AVs, which are beneficial to data encryption and transmission without mutual interference of AVs of different orders. The favorable results provide theoretical bases and technical support to data transmission and OAM decoding for the OAM communication of AV beams using simplified single-ring transceiver arrays.